AGRITOURISM AS A MANIFESTATION OF POLISH TOURISM - Wojciechowska, Jolanta (Acta Scientiarum Polonorum. Oeconomia, 2010)
The aim of the article is to show that agritourism is a particular manifestation of Polish tourism in rural areas, which has been developing part of market economy since 1989. Firstly the author attempts to explain why agritourism can be regarded as a manifestation and then to describe it. Therefore she discusses the features of Polish agritourism and next the role of the factors which generate it, as well as development consequences. It is stated that agritourism in Poland, both as a term and a type of tourism, is a new phenomenon, initiated institutionally at time of political and economic transformation in our country. Thus it is manifested by certain socio-political conditions and mechanisms, which made it a type of tourism that socially developed from scratch, while from the geographical point of view (nature and landscape) it continues the tradition of recreation in rural areas (succession of the recreational function of an area). It is assumed that the process of agritourism development consists in two paradigms: the old one, where exogenic factors were crucial, and the new one, where creativity based on experience is a priority.